Aquatic Ecological Index based on freshwater (ICERN-MAE) for the Río Negro watershed, Colombia. - Forero, Laura Cristina; Longo, Magnolia; Ramírez R., John Jairo; Chalar, Guillermo (Revista de Biología Tropical, 2014)
Available indices to assess the ecological status of rivers in Colombia are mostly based on subjective hypotheses about macroinvertebrate tolerance to pollution, which have important limitations. Here we present the application of a method to establish an index of ecological quality for lotic systems in Colombia. The index, based on macroinvertebrate abundance and physicochemical variables, was developed as an alternative to the BMWP-Col index. The method consists on determining an environmental gradient from correlations between physicochemical variables and abundance. The scores obtained in each sampling point are used in a standardized correlation for a model of weighted averages (WA). In the WA model abundances are also weighted to estimate the optimum and tolerance values of each taxon; using this information we estimated the index of ecological quality based also on macroinvertebrate (ICERN-MAE) abundance in each sampling site. Subsequently, we classified all sites using the index and concentrations of total phosphorus (TP) in a cluster analysis. Using TP and ICERN-MAE, mean, maximum, minimum and standard deviation, we defined threshold values corresponding to three categories of ecological status: good, fair and critical. Rev. Biol. Trop. 62 (Suppl. 2): 233-247. Epub 2014 April 01.